Application of Diabetes Self-Management Education and Support in Outpatients with Type II DM - Indah Ratnasari; Iskari Ngadiarti; Lilik Fauziyah Ahmad (Universitas Airlangga, 2022)
Education through self-management and support plays an important role in providing knowledge and instilling an awareness of the importance of healthy living. The purpose of this study was to determine the effect of Diabetes Self-Management Education and Support on eating habits, body weight, nutritional status, and glycemic control. The design of this study was quasi-experimental with the experimental design of the Pre Test Post Test without a control group. The number of samples was 60 patients who were taken by purposive sampling with predefined inclusion and exclusion criteria. Interventions were conducted 2 times a month for 6 months. From this study, it is known that for 6 months there was an increase in the consumption of vegetables, fruit, and milk (p<0,05), a significant decrease in the consumption of tubers and starches (p <0.05), while the consumption of rice and side dishes did not experience a significant change (p> 0, 05). Besides, there was a significant decrease in glycemic control (p <0.05) but there was no significant reduction in body weight and nutritional status (p> 0.05). The application of Diabetes Self-Management Education and Support for 6 months can influence glycemic control and change eating habits.